Cost Analysis in Shoulder Arthroplasty Surgery - Teusink, Matthew J. (Hindawi Publishing Corporation, 2012)
Cost in shoulder surgery has taken on a new focus with passage of the Patient Protection and Affordable Care Act. As part of this law, there is a provision for Accountable Care Organizations (ACOs) and the bundled payment initiative. In this model, one entity would receive a single payment for an episode of care and distribute funds to all other parties involved. Given its reproducible nature, shoulder arthroplasty is ideally situated to become a model for an episode of care. Currently, there is little research into cost in shoulder arthroplasty surgery. The current analyses do not provide surgeons with a method for determining the cost and outcomes of their interventions, which is necessary to the success of bundled payment. Surgeons are ideally positioned to become leaders in ACOs, but in order for them to do so a methodology must be developed where accurate costs and outcomes can be determined for the episode of care.